KUALITAS KREDIT PADA INDUSTRI PERBANKAN DAN DAMPAKNYA TERHADAP PROFITABILITAS BANK (Studi Empirik pada Bank Umum Konvensional yangTerdaftar diBursa Efek Indonesia) - Dewi Sri Handayani; Bambang Sudiyatno (Jurnal Bisnis dan Ekonomi, 2017)
This study aims to test and analyze the factors that affect the quality of credit that is, the influence of CAR, LDR, SIZE, BOPO to NPL and its impact on ROA. Analysis of research data is done by using multiple regression method. While the sampling method is done by purposive sampling method. The study was conducted at Indonesia Stock Exchange, with period of 2013 until 2015.The results show that Capital Adequacy Ratio (CAR) has no effect on Non Performing Loan (NPL). Loan to Deposit Ratio (LDR), Bank size (SIZE), and Bank Operating Cost (BOPO) have a significant positive effect on Non Performing Loan (NPL). While Non Performing Loan (NPL) has a significant negative effect on Return On Assets (ROA). Keywords: Capital Adequacy Ratio, Loan to Deposit Ratio, BOPO, SIZE, Non Performing Loan and Return On Asset